الكفاءة الذاتية للعاملين في المؤسسات التعليمية: المحددات والمرتكزات: Self-efficacy of Employees in Educational Institutions: Determinants and Pillars - جمال المبروك المناع (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تهدف الدراسة إلى التعرف على الكفاءة الذاتية للعاملين في المؤسسات التعليمية الليبية. وتكمن مشكلة الدراسة في تدني الكفاءة الذاتية للعاملين في المؤسسات التعليمية الليبية، مما يؤثر سلباً على الأداء الوظيفي للعاملين في هذه المؤسسات. وتبرز أهمية الدراسة في تسليط الضوء عناصر الكفاءة الذاتية الواجب استخدامها في كافة المؤسسات التعليمية الليبية. واتبعت الدراسة المنهج الوصفي التحليلي لوصف وتحليل الكفاءة الذاتية للعاملين في المؤسسات التعليمية الليبية. ولقد توصلت الدراسة إلى العديد من النتائج من بينها أن الكفاءة الذاتية لها دور بارز في تحسين الأداء الوظيفي للعاملين في المؤسسات التعليمية الليبية، كما أوضحت نتائج الدراسة أن من أبرز محددات الكفاءة الذاتية هي الحبرات السابقة يمكن للعاملين استخدامها في كافة المواقف التي تواجههم داخل المؤسسات التعليمية الليبية. وكذلك فإن نتائج الدراسة خلصت إلى إمكانية استخدام الإقناع اللفظي في إبراز الكفاءة الذاية في العمل، كما أوضحت نتائج الدراسة أن التأثر العاطفي من أبرز محددات الكفاءة الذاتية، وكذلك التجارب السابقة من أبرز محددات الكفاءة الذاتية في المؤسسات التعليمية الليبية. كما أوضحت النتائج أن الموظفين والبيئة التنظيمية من أهم مرتكزات الكفاءة الذاتية بالمؤسسات التعليمية الليبية. وأوصت الدراسة بضرورة العمل على اتاحة الفرصة للموظفين لإيضاح الكفاءة الذاتية لديهم والعمل على تحسين أداء المؤسسات التعليمية الليبية بشكل كبير. Abstract The study aims to identify the self-efficacy of workers in Libyan educational institutions. The problem of the study lies in the low self-efficacy of workers in Libyan educational institutions, which negatively affects the job performance of workers in these institutions. The study highlights the importance of highlighting the elements of self-efficacy to be used in all Libyan educational institutions. The study followed the descriptive analytical approach to describe and analyze the self-efficacy of workers in Libyan educational institutions. The study reached many results, including that self-efficacy has a prominent role in improving the job performance of workers in Libyan educational institutions. The results of the study also showed that one of the most prominent determinants of self-efficacy is the previous experience that workers can use in all the situations they face within the Libyan educational institutions. Also, the results of the study concluded that verbal persuasion can be used to highlight self-efficacy at work, and the results of the study showed that emotional influence is one of the most prominent determinants of self-efficacy, as well as previous experiences of the most prominent determinants of self-efficacy in Libyan educational institutions. The results also showed that employees and the organizational environment are among the most important pillars of self-efficacy in Libyan educational institutions. The study recommended the necessity of working to provide the employees with the opportunity to clarify their self-efficacy and work to improve the performance of Libyan educational institutions significantly.